Connecting solar flare hard X-ray spectra to in situ electron spectra A comparison of RHESSI and STEREO/SEPT observations - Dresing N; Warmuth A; Effenberger F; Klein KL; Musset S; Glesener L; Brudern M (EDP SCIENCES S A, 2022)
Aims. We aim to constrain the acceleration, injection, and transport processes of flare-accelerated energetic electrons by comparing their characteristics at the Sun with those injected into interplanetary space.Methods. We have identified 17 energetic electron events well-observed with the SEPT instrument aboard STEREO which show a clear association with a hard X-ray (HXR) flare observed with the RHESSI spacecraft. We compare the spectral indices of the RHESSI HXR spectra with those of the interplanetary electrons. Because of the frequent double-power-law shape of the in situ electron spectra, we paid special attention to the choice of the spectral index used for comparison.Results. The time difference between the electron onsets and the associated type III and microwave bursts suggests that the electron events are detected at 1 AU with apparent delays ranging from 9 to 41 min. While the parent solar activity is clearly impulsive, also showing a high correlation with extreme ultraviolet jets, most of the studied events occur in temporal coincidence with coronal mass ejections (CMEs). In spite of the observed onset delays and presence of CMEs in the low corona, we find a significant correlation of about 0.8 between the spectral indices of the HXR flare and the in situ electrons. The correlations increase if only events with significant anisotropy are considered. This suggests that transport effects can alter the injected spectra leading to a strongly reduced imprint of the flare acceleration.Conclusions. We conclude that interplanetary transport effects must be taken into account when inferring the initial acceleration of solar energetic electron events. Although our results suggest a clear imprint of flare acceleration for the analyzed event sample, a secondary acceleration might be present which could account for the observed delays. However, the limited and variable pitch-angle coverage of SEPT could also be the reason for the observed delays.